Development of Tahsin Tahfidz Media Innovation “Memo Qur'an” inImproving Reading Literacy and Digital Literacy of Students - Mamlu'ah, Aya; Rahmawati, Ulva Badi’; Jalil, Abdul (Ahlussunnah: Journal of Islamic Education, 2025)
The digital era, which facilitates internet access, creates challenges and opportunities for the world of education, demanding innovation to shift conventional practices towards more advanced ones. Literacy, as a fundamental competency that includes the ability to access, interpret, evaluate, and utilize information, has become crucial among students. This study aims to develop a digital-based Tahsin Tahfidz learning media innovation called “Memo Qur'an” to improve students' reading and digital literacy. This study uses the Research and Development method with the Analysis, Design, Development, Implementation, Evaluation model at level 4, which aims to create new products and test their effectiveness. Data was collected through in-depth interviews and questionnaires involving lecturers and students. The validation results from subject matter experts and media experts showed that this application was highly feasible with feasibility percentages of 96.88% and 88.4%, respectively. Practicality tests by lecturers and students also produced very feasible scores, with an average of 91.2% from students and 100% from lecturers. The implications of the study show that “Memo Qur'an” is a very feasible and practical media innovation to improve students' reading literacy and digital literacy, and can be widely downloaded through the Play Store to support adaptive learning in the digital era.